Features of circuitry of acousto-optic laser measuring systems for controlling three-coordinate (3D) movements of products and equipment elements. Part 2 - E. V. Leun (Омский научный вестник)
The article discusses the noise, dynamic and accuracy parameters of acousto-optical (AO) laser measuring systems (LMS) for high-precision control of three-coordinate (3D) displacements of products. It is shown that now when using modern high-speed low-noise photodetectors makes it possible to achieve the resolution of AO LMS without special technical techniques for longitudinal Δlx and transverse Δly , Δlz displacements, respectively, where λ and Λaom are the wavelength of light and sound in the AO modulator. The features of using PLL systems in AO LMS are discussed. The possibilities of increasing the resolution when measuring displacements using two photodetectors for one input optical signal: high-speed and low-noise, as well as by controlling the bandwidth of the PLL system are considered.